Work Climate and Occupational Fatigue among Furniture Workers - Ekasari, Ranti; Insan Sakinah, Magfirah; Rahmi, Suci; Sasmita, Nur; Wahab, Muh. Abdul; Widiastuty, Lilis (Universitas Islam Negeri Alauddin Makassar, 2026)
Work climate refers to the interaction of environmental factors in the workplace. Fatigue is a common occupational health issue and can be affected by multiple factors such as work climate, age, gender, length of employment, and daily working duration. This study aimed to examine the relationship between work climate and work fatigue among furniture workers in Hertasning, Indonesia. A quantitative analytical study with a cross-sectional design was conducted in several furniture workshops in December 2023. The study involved 30 furniture workers selected through purposive sampling. Data were collected using the questionnaire to assess subjective feelings of work fatigue and a Heat Stress Monitor to measure workplace climate conditions. The results showed a statistically significant relationship between work climate and work fatigue (p = 0.028; p < 0.05), indicating that workers exposed to unfavorable work climate conditions were more likely to experience fatigue. These findings suggest that work climate plays an important role in influencing workers’ fatigue levels. Therefore, it is recommended that furniture business owners improve workplace comfort by providing adequate rest areas with appropriate temperature control and installing cooling facilities, such as fans, to reduce heat exposure and prevent work-related fatigue.